SOCIAL ACCOUNTING QUALITY IMPLEMENTATION: A SOLID FOUNDATION FOR BUSINESS SUSTAINABILITY - soonthonrot, pakaphon; เชียรวัฒนสุข กฤษดา (Thai Interdisciplinary and Sustainability Review, 2023)
Social accounting is the accounting discipline of providing information in corporate operations through financial reports in a variety of formats, all of which are designed to communicate social responsibility information to stakeholders gain knowledge about information that businesses voluntarily give to society and stakeholders with the business in order to create a good image for the business to benefit society and the environment for economic and social decision making. Entrepreneurs should prioritize social responsibility. In order to truly respond to societal expectations, particularly for companies listed on the Thai Stock Exchange. This is a business that requires a great deal of acceptance and faith from society, which will have an impact on the success of long-term goals. to improve sales, income, and financial standing Increasing business profits consistently. Growth in investment and market share in comparison to previous performance Creating a Competitive Advantage Developing positive connections with all stakeholders while adding company value via social and environmental responsibility. The quality of social accounting application is therefore like a tool to assist the firm function constantly and sustainably.